2022
DOI: 10.25159/1947-9417/8926
|View full text |Cite
|
Sign up to set email alerts
|

If Not in Science, Then Where Are the Women? A Content Analysis of School Textbooks

Abstract: This article analyses the representation of femininity in school textbooks in search of elements that discourage girls from taking up scientific educational paths. Quantitative content analysis and elements of the constant comparison method were used to examine the content of 75 Polish textbooks. Significant differences were identified in the number of male and female characters, their ages, financial resources, occupations, family roles and mental characteristics. Interestingly, the authors of the analysed te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The interviewees were asked to answer the questions as broadly as possible. The questions included in the interview questionnaire were formulated on the basis of research on gender stereotypes in a school environment [ 66 68 ], teachers’ attitudes towards students [ 43 , 63 , 69 ] and gender bias analyses in school textbooks [ 37 , 38 ]. The final version of the interview questionnaire included ten questions corresponding to the four main research questions presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviewees were asked to answer the questions as broadly as possible. The questions included in the interview questionnaire were formulated on the basis of research on gender stereotypes in a school environment [ 66 68 ], teachers’ attitudes towards students [ 43 , 63 , 69 ] and gender bias analyses in school textbooks [ 37 , 38 ]. The final version of the interview questionnaire included ten questions corresponding to the four main research questions presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Male characters usually deal with exact sciences, study and practise professions that require mental work, while female characters choose activities related to artistic activities. Unlike men, they are not decision-making or enterprising, and more often require assistance with various activities [ 38 ].…”
Section: Increasing Gender Stereotypes At Schoolmentioning
confidence: 99%
“…63–64). The gender representation in school textbooks was unbalanced during the totalitarian socialist regime as well as task division was also gender-biased (Gajda and Wolowicz, 2022). Gender stereotyping is still a problem in Polish school textbooks published more recently.…”
Section: Research Conducted In Post-soviet Post-socialist and Post Au...mentioning
confidence: 99%
“…Gender stereotyping is still a problem in Polish school textbooks published more recently. Chmura-Rutkowska et al (2016) identified that in Polish school textbooks, “Women more often took care of the household and family, while men earned more and they more regularly held managerial positions” (Gajda and Wolowicz, 2022, p. 4). Based on an analysis of different studies, Zamojska (2016, p. 672) concludes that “Gender differences are essentialized and burdened by stereotypes; most texts depict women and men in accordance with the traditional model of their social functioning, based on gender inequality”.…”
Section: Research Conducted In Post-soviet Post-socialist and Post Au...mentioning
confidence: 99%